KONFLIK TOKOH DALAM NOVEL LAPAR KARYA ERBY S. - Rani Anggita Sari; Totok Priyadi; Agus Wartiningsih (Universitas Tanjungpura, 2022)
This study aims to describe and interpret the results of the analysis of internal and external conflicts in the novel Lapar by Erby S. as well as the preparation of learning plans using the novel as learning material. This research applied the descriptive method with a qualitative research form. This study uses a psychological approach to behaviorism literature. The data source in this research is the novel Lapar by Erby S. and this research is the form of internal and external conflicts in the form of words, phrases, or sentences contained in the novel. The technique of data collection used a documentary study technique with the researcher as a data collection tool. The results of the study are 33 data.such as 29 internal conflicts and 4 external conflicts. The finding of this research showed :First the internal conflicts of the characters are events that cause feelings of anger, regret, fear, anxiety, confusion, sadness. Second External conflicts of characters, namely conflicts that arise due to physical clashes between characters. Preparation of Learning Implementation Plans (RPP) with competence 3.9 Identifying the content (intrinsic elements) in novels and 4.9 Designing novels or novelets by paying attention to content and language in class XII SMA by using the novel Lapar by Erby S. as Bahasa Indonesia learning materials.